Synthesis, Characterization and Antimicrobial Activity - RAJIV DUA,; S.K. SRIVASTAVA, (International Journal of Pharma and Bio Sciences, 2010)
As a part of systematic investigation of synthesis and biological activity of several new 2-(2'-substituted-benzylidene-hydrazino-acetyl)-mercapto-5-methyl-1,3,4-thiadiazoles, 3(a-n) and 2-[2'-{4-substituted-aryl-3-chloro-2-oxo-azetidine}-acetyl-amino-mercapto]-5-methyl-1,3,4-thiadiazoles, 4(a-n) have been synthesized from 2-(2'-hydrazino-acetyl)-mercapto-5-methyl-1,3,4-thiadiazoles, 2 using 5-methyl-1,3,4-thiadiazole-2-thiol as the starting material. All the synthesized products were evaluated for their antibacterial activity against Bacillus substilis, Escherichia coli. Klebsiella pneumoniae and Streptococcus aureus bacteria and antifungal activity against Aspergillus niger, Aspergillus flavus, Fusarium oxisporium and Trichoderma viride fungi respectively. The structures of all the synthesized compounds have been determined by their spectral and microanalytical data.